STUDENTS’ KNOWLEDGE AND RISK OF COMMITTING MEDICATION ERRORS IN TWO SCHOOLS OF PHARMACY IN NIGERIA - CM, UBAKA; C, EKWE; A, ISAH; AB, MUKHTAR; CV, UKWE (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this study was to determine the knowledge of prescription errors, the certainty of such knowledge, and the risk of committing medication errors among pharmacy students in two universities in Nigeria. Methods: This study was a cross-sectional comparative survey between pharmacy students of two universities in Nigeria: University of Nigeria, Nsukka (UNN) and Nnamdi Azikiwe University (NAU), Awka. Study variables were measured using four simulated prescriptions and questionnaires. Chi-square test, independent t-test, and ordinal regression analyses were used to assess study outcomes. Results: A total of 339 pharmacy students (239 in UNN and 100 in NAU), with a mean age of 24 (2.8) years and 57.2% (n=194) male students, participated in this study. Their accurate knowledge of each of the prescriptions were 294 (86.72%), 166 (48.97%), 199 (58.70%), and 248 (73.16%) for prescriptions with error of drug allergy, error of drug interaction, no error, and wrong dose of a drug, respectively. Students from UNN were more likely to commit a statistically significant high risk of error compared to NAU students in prescriptions with a drug allergy and wrong dose, while students in the 4th year class had a statistically significant higher odds of committing a drug interaction prescription error compared to final year students. Conclusion: Pharmacy students evaluated in this study had good knowledge of medication error detection. The risk of these pharmacy students committing a prescription error was evident in nearly all prescriptions tested and the students’ school was the major predictor of these risks.